Evaluating the Correlation between High Titers of Tissue-Transglutaminase Antibody with the Grade of Severity of Villous Atrophy in Syrian Patients with Celiac Disease - A. Alhabbal; I. Abou Khamis (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Background. Diagnosis of celiac disease depends on the patient’s history and serological tests, and is confirmed by biopsies from the duodenum. Biopsies from the small intestine could be dispensable regarding the verification of celiac disease with the presence of high levels of atissue-transglutaminase antibody.Aim. The objective of this investigation is to substantiate the correlation between titers of anti-tissue transglutaminase type IgA (anti-tTG IgA) and the severity of histological alterations in Syrian patients with celiac disease and to determine the diagnostic level of anti-tTG to previse celiac disease in adults and children without the necessity of a biopsy sampling.Materials and methods. The study was conducted as a prospective cohort study with the participation of 100 symptomatic patients between the age group of 6–65 years. All participants underwent upper gastrointestinal endoscopy. Two samples were taken from the duodenum and were evaluated by an expert pathologist according to Marsh grading. Serum anti-tTG IgA levels were measured as well to determine any association between the levels of serum anti-tTG IgA and Marsh grading.Results. The mean age of the patients was (18.55 ± 12.92). Anemia was the most frequent non-gastrointestinal finding as it was found among 35% of the participant, but no remarkable association was found between Marsh grading and hemoglobin levels (r = 0.36, p > 0.05). However, serum tTGA levels were positively correlated with Marsh grading (r = 0.718, p < 0.001). Receiver-operator curve (ROC) analysis cut-off value of serum anti-tTGA for speculating villous atrophy was 270 IU/ml of cut-off value with a sensitivity of 100% and a specificity of 89%.Conclusion. Duodenal biopsies could be foregone during the diagnosis of susceptible patients for celiac diseasewith high anti-tTG IgA.